2019
DOI: 10.1021/acs.molpharmaceut.8b01197
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Macromolecular Analgesic for Arthritic Pain

Abstract: The addictive potential of clinically-used opioids due to their direct action on the dopaminergic reward system in the brain has limited their application. In an attempt to reduce negative side effects as well as to improve the overall effectiveness of these analgesics, we have designed, synthesized, and evaluated an N-(2-hydroxypropyl)methacrylamide (HPMA)-based macromolecular prodrug of hydromorphone (HMP), a commonly used opioid. To this end, P-HMP was synthesized via RAFT polymerization and a subsequent po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…With the introduction of a neighboring benzene ring next to the hydrazone bond, an electron conjugation was produced, which stabilized the linker and slowed down its cleavage 44 and HMP release, contributing to a more sustained local analgesic effect than the previously reported P-HMP. 38 The newly synthesized ProGel-HMP has a weight-average molecular weight (M w ) of 12.5 kDa with a narrow dispersity (Đ = 1.03). Its aqueous solution (20 w/v%) is thermoresponsive (Figure 1A), transitioning from a free-flowing fluid at 4 °C to a hydrogel at 37 °C.…”
Section: Molecularmentioning
confidence: 99%
See 2 more Smart Citations
“…With the introduction of a neighboring benzene ring next to the hydrazone bond, an electron conjugation was produced, which stabilized the linker and slowed down its cleavage 44 and HMP release, contributing to a more sustained local analgesic effect than the previously reported P-HMP. 38 The newly synthesized ProGel-HMP has a weight-average molecular weight (M w ) of 12.5 kDa with a narrow dispersity (Đ = 1.03). Its aqueous solution (20 w/v%) is thermoresponsive (Figure 1A), transitioning from a free-flowing fluid at 4 °C to a hydrogel at 37 °C.…”
Section: Molecularmentioning
confidence: 99%
“…This physical mechanism for the local retention and gradual release of ProGel-HMP and the use of a more stable hydrazone linker for HMP conjugation are most likely responsible for its drastically improved duration of analgesia when compared to P-HMP. 38 The chronic nature of joint pain associated with the DMM model enables testing of the analgesic effect of ProGel-HMP and its potential for tolerance development. While it is a plausible option for temporary pain relief of acute arthritis pain flare in human subjects with OA joint pain, the 14-day local analgesia duration offered by ProGel-HMP in this study is unlikely to be applicable for general management of chronic OA pain, even with the potential adjustment of the duration by introducing a hydrophobic counterion.…”
Section: Molecularmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that vitamin C plays a significant protective role by maintaining the antioxidant activity of hydroxyl oxidase and reducing reactive oxygen species and tissue oxidative damage. In addition, it can inhibit the triptolide-induced apoptosis in renal tubular epithelial cells by inhibiting the occurrence of oxidative stress (Dennis & Witting, 2017 ; Xu et al., 2019 ). Here, triptolide loaded nanoparticles were prepared by using vitamin C derivatives as the carrier, which could reduce some side effects of TP and guarantee the therapeutic effect for RA.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cartilage and bone damage is caused by osteoclasts, activated synovial fibroblasts and chondrocytes in inflammatory arthritis [3]. Currently available anti-rheumatic drugs, including non-steroidal drugs, glucocorticoids, and biological agents, cannot cure RA radically but only relieve its symptoms and progression [4,5]. In China, herbal medicines have been extensively utilized as alternative RA drugs for decades [6,7].…”
Section: Introductionmentioning
confidence: 99%